1993
DOI: 10.1021/ja00063a008
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclization under thermodynamic control. A theoretical study and its application to the equilibrium cyclooligomerization of .beta.-propiolactone

Abstract: A general treatment of macrocyclization reactions occurring under thermodynamic control is presented. The fundamental quantities on which the treatment is based are the effective molarities of the cyclic oligomers and the equilibrium constant for the intermolecular model reaction between monofunctional reactants (Kinter). Four typical cases have been considered, namely, addition and condensation of a monomer of the type A-B, addition of A-A, and addition of A-A + B-B. A critical comparison with the classical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
231
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(241 citation statements)
references
References 1 publication
9
231
1
Order By: Relevance
“…Ercolani has extended the Jacobson and Stockmayer theory 113 for cyclic and linear species in step-growth covalent polymers in order to correlate K inter and K intra to weight and number averaged degrees of polymerization. 114 Already in the first report of UPy based supramolecular polymers, Sijbesma and Meijer showed that the concept of chain stopper can be successfully applied to self-assembled macromolecules. 3 By dissolving a small amount of a low-molecularweight bifunctional UPy1-C 6 -UPy1 in chloroform a solution with a high specific viscosity g sp was obtained (Fig.…”
Section: End-capping Of Supramolecular Polymersmentioning
confidence: 99%
“…Ercolani has extended the Jacobson and Stockmayer theory 113 for cyclic and linear species in step-growth covalent polymers in order to correlate K inter and K intra to weight and number averaged degrees of polymerization. 114 Already in the first report of UPy based supramolecular polymers, Sijbesma and Meijer showed that the concept of chain stopper can be successfully applied to self-assembled macromolecules. 3 By dissolving a small amount of a low-molecularweight bifunctional UPy1-C 6 -UPy1 in chloroform a solution with a high specific viscosity g sp was obtained (Fig.…”
Section: End-capping Of Supramolecular Polymersmentioning
confidence: 99%
“…19 In applying the theory to describe experimental systems, the assumption of strainless rings is not always met.…”
Section: Model Outlinementioning
confidence: 99%
“…19 Thus, in effect, component buffering is caused by competition between ring formation by UPy-UPy association and end-capping by UPy-NaPy binding. This competition also explains why the onset of the buffering plateau -and concurrently UPy-NaPy binding -occurs at a much higher concentration than the binding of monotopic UPy and NaPy (K UPy-NaPy = 5 .…”
Section: Model Outlinementioning
confidence: 99%
“…5,6 Ditopic supramolecular compounds have the ability to form either rings (K intra ) or linear polymers (K inter ), where the stability of the rings can be defined by the effective molarity (EM = K intra / K inter ). 7,8 Since the EM represents a local concentration, the formation of intramolecular contacts, i.e. rings, is more favorable at low concentrations, while polymerization is favored at high concentrations.…”
Section: Introductionmentioning
confidence: 99%